2017
DOI: 10.3892/or.2017.5440
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-penetrating peptide fused to a pro-apoptotic peptide facilitates effective gastric cancer therapy

Abstract: KLA (sequence, KLAKLAKKLAKLAK) is a peptide which leads to programmed cell death by disrupting the mitochondrial membrane. However, low penetration in tumors greatly limits its application and efficacy. To develop a KLA-based cancer therapy, KLA-iRGD, a recombinant protein was constructed. It consists of the KLA peptide and iRGD (CRGDKGPDC), a tumor-homing peptide with high penetration into tumor tissue and cells. The conjugated KLA exhibits pro-apoptotic activity to prevent the growth of a tumor once it is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Anticancer peptides act as either molecularly targeted peptides, which can penetrate and directly bind to the specific cancer cell or organelle membranes, or binding peptides linking to the anticancer drugs (35)(36)(37). In cancer cells, anticancer peptides, as molecular targeting peptides, particularly in the α-helical form, penetrate the plasma membrane, the nuclear membrane and/or the mitochondrial membrane exerting pharmacological activity via different mechanisms (such as the inhibition of DNA synthesis or cell division), thus promoting cancer cell apoptosis (38)(39)(40)(41). However, binding peptides, also referred to as cancer-targeting peptides or cell-penetrating peptides, that have no anticancer property, can recognize and penetrate the cancer cell membrane (42).…”
Section: Anticancer Peptide: Physicochemical Property Functional Aspmentioning
confidence: 99%
See 3 more Smart Citations
“…Anticancer peptides act as either molecularly targeted peptides, which can penetrate and directly bind to the specific cancer cell or organelle membranes, or binding peptides linking to the anticancer drugs (35)(36)(37). In cancer cells, anticancer peptides, as molecular targeting peptides, particularly in the α-helical form, penetrate the plasma membrane, the nuclear membrane and/or the mitochondrial membrane exerting pharmacological activity via different mechanisms (such as the inhibition of DNA synthesis or cell division), thus promoting cancer cell apoptosis (38)(39)(40)(41). However, binding peptides, also referred to as cancer-targeting peptides or cell-penetrating peptides, that have no anticancer property, can recognize and penetrate the cancer cell membrane (42).…”
Section: Anticancer Peptide: Physicochemical Property Functional Aspmentioning
confidence: 99%
“…Based on the mechanism of entry, therapeutic peptides are also classified into three groups based on their biological targets, including: i) Signal transduction pathways; ii) cell cycle regulation; and iii) cell death pathways (92,93). For instance, a tumor-penetrating peptide, KLA, exerts pro-apoptotic activity, which disrupts the mitochondrial membrane, leading to programmed cell death in tumors (40). In a tumor suppressor mechanism, kisspeptin-1 metastasis suppressor, a precursor for several shorter peptides, which regularly exhibits decreased expression in metastatic tumors, can suppress colonization of disseminated cancer cells in distant organs and is involved in mechanisms of tumor angiogenesis, autophagy and apoptosis regulation in breast cancer (94).…”
Section: Classification Of Acpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that iRGD improves the activity and specificity of several anticancer peptides, including ATAP 15 , m(KLA) 16 , TP5 17 , CDD 18 and D (KLA) 2 19 , by conjugating with these peptides. Kazuki et al .…”
Section: Introductionmentioning
confidence: 99%